Choosing A Career: A Students' Guide - Sijiwola, I.O. (Evans Brothers (Nigeria Publishers) Ltd, 2009)
Choosing a career is written to assist students to be able to choose their careers correctly while parents, teachers and guidance counsellor will be better equipped to assist their children and wards in making their right choice.
Keywords: Juvenile Non-Fiction / Choosing Career